Liturgical music and faith formation: the role of Javanese musical inculturation in congregational religious awareness - Juanita Theresia Adimurti; Sunarto Sunarto; Udi Utomo (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
This study examines the pedagogical and theological functions of musical inculturation in Catholic faith education. Drawing on post–Vatican II principles of contextual liturgy, the research analyzes how Javanese musical elements, particularly gamelan textures and macapat melodic patterns, are integrated into Catholic worship to support cognitive comprehension, affective engagement, and active congregational participation. Using a qualitative design involving in-depth interviews, participant observation, and document analysis, the study employs thematic analysis to identify how inculturated music shapes faith formation. The findings show that inculturated musical practices enhance three measurable dimensions of faith education: (1) cognitive understanding, demonstrated by a clearer grasp of liturgical texts expressed in culturally familiar musical forms; (2) affective devotion, indicated by heightened emotional resonance and spiritual focus during worship; and (3) participatory involvement, reflected in increased vocal and embodied participation of congregants. The study also identifies a persistent tension between maintaining universal liturgical norms and embracing local cultural expressions, revealing an ongoing negotiation between ecclesial identity and Javanese cultural values. The novelty of this research lies in demonstrating that musical inculturation functions as a form of nonverbal religious pedagogy, simultaneously strengthening Catholic doctrinal understanding and affirming local cultural identity. This contributes to interdisciplinary discussions in theology, pedagogy, and ethnomusicology by offering an empirically grounded model of how liturgical music can operate as an effective medium for contextual faith education.